Comparison of metoclopramide–dexamethasone combination and metoclopramide alone for prophylaxis of postoperative nausea vomiting in laparoscopic cholecystectomy - Humaira Ahmad; Sarwat Bibi; Samina Aslam; Asif Sagheer (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Post operative nausea and vomiting (PONV) is an important concern in laparoscopic surgeries. Aim of this study is to identify the role of metoclopramide dexamethasone combination for prophylactic management of post laparoscopic cholecystectomy nausea and vomiting in comparison to metoclopramide alone. METHODOLOGY: The study group comprised of 150 patients. These were the patients with symptomatic gallstones for whom elective laparoscopic cholecystectomy was planned. Study was conducted from 15-04-2018 to 15-07-2019. Non-probability consecutive sampling technique was used.Two groups were generated by simple random method. Group M was given injection metoclopramide only, whereas patients in Group D+M were injected with both dexamethasone and metoclopramide, intravenously, before induction of anesthesia. Parameters observed for 24 hours during postoperative period included; nausea, episodes of vomiting, requirement for rescue antiemetic drugs and total duration of hospital stay after the surgical procedure. RESULTS: In Group D+M (dexamethasone+metoclopramide), out of total 75 patients, 8% developed nausea while 5.33% had both nausea along with emesis. While in group M (metoclopramide), 16% out of the total 75 patients had nausea only but 18.7% patients had complaints of nausea and emesis. Three patients out of 75, that is (4%) from group (D+M) had extended duration of in hospital admission (> 24 hours), while in group M, this percentage was 13.33% that is 10 patients. CONCLUSION: A combination of metoclopramide with dexamethasone for prophylaxis against PONV in laparoscopic cholecystectomy patients is preferred to metoclopramide alone.